2016
DOI: 10.1111/ijfs.13286
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficiency of different food‐grade emulsifiers to form and stabilise orange oil‐in‐water beverage emulsions: influence of emulsifier concentration and storage time

Abstract: The aim of this study was to compare the efficiency of three different food-grade emulsifiers to form and stabilise an orange oil-in-water emulsion. The emulsifier type and concentration had a profound effect on the initial particle size of the oil droplets with Tween 80 being the most effective in reducing the particle size (1% w/w, 1.88 AE 0.01 lm) followed by sodium caseinate (10% w/w, 2.14 AE 0.03 lm) and gum arabic (10% w/w, 4.10 AE 0.24 lm). The long-term stability of the concentrated beverages was monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 38 publications
(47 reference statements)
1
27
0
1
Order By: Relevance
“…The physical stability of mayonnaise samples was monitored using a Turbiscan MA2000 apparatus (Formulaction, Ramonville‐St‐Agne, France) as described by Raikos et al () with slight modifications. The sample in the cell was scanned every 5 min for 30 min at 40 °C, and the changes in the intensity of the backscattered light (ΔBS) in unit time were taken as a measure of the stability of the emulsions.…”
Section: Methodsmentioning
confidence: 99%
“…The physical stability of mayonnaise samples was monitored using a Turbiscan MA2000 apparatus (Formulaction, Ramonville‐St‐Agne, France) as described by Raikos et al () with slight modifications. The sample in the cell was scanned every 5 min for 30 min at 40 °C, and the changes in the intensity of the backscattered light (ΔBS) in unit time were taken as a measure of the stability of the emulsions.…”
Section: Methodsmentioning
confidence: 99%
“…It was intended to pick the sample with possibly the lowest oxidative stability so that the effect of BCD addition would be clearer. Protein-based emulsifiers are reported to have antioxidant activities (Kiokias et al, 2006, McClements & Decker, 2000Raikos et al, 2017;Sorensen et al, 2007). Nonadsorbed protein emulsifiers are known to interact with water-soluble reagents such as free radicals or metal ions (Cheng, Xiong, & Chen, 2010).…”
Section: Effect Of Bcd On Physical and Oxidative Stability Of Citrem-mentioning
confidence: 99%
“…Type of the emulsifier used has been shown to influence both physical and chemical stability of O/W emulsions (Haahr & Jacobsen, 2008;Horn et al, 2011;Nielsen, Horn, & Jacobsen, 2013;Raikos, Duthie, & Ranawana, 2017). Milk protein-based emulsifiers, such as caseins and whey proteins, are widely used in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins especially from milk and eggs can act as emulsifiers, since it has been demonstrated that they can adsorb at the oil/water interface to protect emulsions from the destabilization phenomena. Nevertheless, proteins tend to adsorb less effectively at the oil/water interface in comparison with small molecule surfactant, so higher amounts of proteins need to be used for emulsion stabilization [25,26]. Recently, Raikos et al [26] observed gravitational separation in sodium caseinate (SC)-stabilized emulsions mainly caused by a lack of surfactant concentration, whereas Tween 80-stabilized emulsions were stable at the same concentration.…”
Section: Effect Of Emulsifier and Stabilizer Type On Beverage Emulsiomentioning
confidence: 99%